The higher education of law in Brazil: The freedom of chair as an instrument of effectiveness to the fundamental right to education - Barbosa, Ronaldo David Viana; Cimolin, Bruno Carminati; Faria, Carolina Duarte Alves de; Cademartori, Luiz Henrique Urquhart; Barbosa, Reinaldo Denis Viana; Beirão, Karina Jansen; Costa, André Laurindo; Zimmermann, Henrique da Silva (Seven Editora, 2024)
The general objective of this article was to present Education as a fundamental right, considering the freedom of professorship as an instrument for the effectiveness of this right. Education that leads the individual to the exercise of citizenship and to the development of the human person invokes freedom in teaching and learning. Highlighting legal education in Brazil, this article also presents the various reforms that have impacted to some extent the content and form of education in the country. The theoretical foundation was divided into 3 sections: i) education as a fundamental right in the Brazilian legal system; ii) legal education in Brazil, reforms and curricular guidelines; iii) university autonomy and freedom of professorship. The research problem consisted in identifying whether the freedom of professorship can be conceived as an instrument of the fundamental right to education. Using a hermeneutic method, the hypothesis initially raised is verified, which gives a positive answer to the problem. DOI:https://doi.org/10.56238/sevened2023.008-030